Review—Inorganic Solid State Electrolytes: Insights on Current and Future Scope. Issue 8 (26th August 2021) - Mishra, Atul Kumar; Chaliyawala, Harsh A.; Patel, Roma; Paneliya, Sagar; Vanpariya, Anjali; Patel, Pratik; Ray, Abhijit; Pati, Ranjan; Mukhopadhyay, Indrajit
Abstract : Lithium-ion-based all solid-state batteries (ASSBs) with inorganic solid-state electrolytes have attracted much attention due to their high energy density, excellent mechanical-electrochemical stability, and lower manufacturing cost. Also, from an environmental perspective ASSBs guarantee a cleaner alternative to fossil-fuel-based applications. Relatively lower Li-ion conductivity of most inorganic solid-state electrolytes and higher electrode-electrolyte interfacial resistance are the most challenging aspects of inorganic solid-state electrolytes. Here, to support researcher's understanding of the inorganic solid-state electrolytes, we have summarized the background and recent advancements in the fundamental understanding of the heart of ASSBs i.e. the inorganic solid electrolytes, by addressing the domains of their structure, Li-ion transport mechanism and the current processing routes. Also, strategies to enhance the performance and stability of ASSBs, the optimization of electrode-electrolyte interfacial resistance are discussed.